Flame-retardant fire-resistant PVC material for new national standard electric vehicle saddle preparation
Patent Information
- Application Number
- CN202611332193.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-31
- Publication Date
- 2026-10-27
AI Technical Summary
[0006]本发明的目的在于提供用于新国标电动车鞍座制备的阻燃耐火PVC材料,用于解决现有聚氯乙烯材料中阻燃组分分散、界面结合、高温耐火防护及柔韧承载之间协同性不足,导致其阻燃耐火性能、高温结构稳定性及力学保持性能有待进一步提高的技术问题
1、本发明制备得到的复合阻燃聚氯乙烯经前序改性及复合处理,使阻燃功能结构预先稳定分布于PVC基体之中,避免了阻燃组分在最终共混过程中直接加入所产生的局部富集,并使材料受热时形成较为连续的阻燃响应;耐火硼硅铝凝胶进一步分散于该基体后,其无机耐火结构能够与复合阻燃聚氯乙烯受热形成的阻隔结构相互衔接,使燃烧区域的热量传递及可燃分解产物逸出受到持续限制,二者的配合并非简单叠加阻燃组分含量,而是在不同受热阶段形成相互补充的防护结构,使材料不易维持持续燃烧,火焰扩展受到抑制;同时,耐火硼硅铝凝胶对受热表层结构的补强,使复合阻燃聚氯乙烯自身的阻燃作用得以更充分地保持。
Smart Images

Figure CN122978633A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of flame-retardant polyvinyl chloride (PVC) materials, specifically to flame-retardant and fire-resistant PVC materials used in the preparation of saddles for electric vehicles meeting the new national standard. Background Technology
[0002] Polyvinyl chloride (PVC) materials are characterized by good flexibility, ease of processing and molding, water resistance, and good surface decoration. They are widely used in electric vehicle saddle coverings, artificial leather, and related flexible components. Existing PVC materials used for electric vehicle saddles are usually based on PVC resin, with plasticizers, stabilizers, fillers, and other functional additives added according to usage requirements to obtain suitable softness, elongation, and processing performance. As the fire safety requirements for electric bicycles continue to increase, the non-metallic materials used in parts such as saddles need to balance user comfort with fire resistance and flame retardancy. Existing flame-retardant PVC usually uses inorganic flame retardants, phosphorus-based flame retardants, silicon-based flame retardants, or composite flame-retardant fillers to achieve corresponding flame-retardant properties while maintaining basic processing and usage performance.
[0003] However, the flame-retardant components in existing flame-retardant PVC materials are mostly dispersed in the polyvinyl chloride matrix in the form of particles or powders. Different components have different polarities, surface properties, and interfacial compatibility with the PVC molecular chains. At higher addition levels, problems such as local aggregation of flame-retardant particles, uneven dispersion, and insufficient interfacial bonding can easily occur. These phenomena can create local stress concentration areas inside the material. When the saddle covering material is subjected to tension, bending, and tearing, interfacial detachment between the flame-retardant particles and the polymer matrix is likely to occur, thereby affecting the material's elongation and tear resistance. Therefore, simply increasing the addition amount of flame-retardant components to enhance the flame-retardant effect makes it difficult to coordinate flame-retardant performance with flexibility and mechanical retention properties, which limits the application effect of flame-retardant PVC in flexible covering materials for electric vehicle saddles.
[0004] Furthermore, when existing flame-retardant PVC materials are exposed to flames or sustained high temperatures, although some flame-retardant components can promote the carbonization of the matrix or form inorganic residues, the resulting high-temperature protective layer is prone to porosity, cracks, and insufficient structural strength, making it difficult to continuously form a complete and dense heat-insulating barrier structure. As the heating time prolongs, the protective layer may shrink, crack, or partially detach, allowing heat to be further transferred into the material. At the same time, combustible decomposition products can easily migrate outward through the pores, limiting the material's ability to inhibit the spread of combustion and the stability of the high-temperature residual structure. Therefore, existing materials still suffer from insufficient synergy in terms of flame retardancy, fire-resistant shielding, high-temperature structural support, and flexible load-bearing capacity, and it is necessary to further improve their comprehensive flame-retardant and fire-resistant properties and mechanical retention properties.
[0005] To address this technical deficiency, a solution is proposed. Summary of the Invention
[0006] The purpose of this invention is to provide a flame-retardant and fire-resistant PVC material for the preparation of electric vehicle saddles in accordance with the new national standard. This material addresses the technical problem that existing polyvinyl chloride materials suffer from insufficient synergy between the dispersion of flame-retardant components, interfacial bonding, high-temperature fire protection, and flexible load-bearing capacity, resulting in the need for further improvement in their flame-retardant and fire-resistant properties, high-temperature structural stability, and mechanical retention.
[0007] The objective of this invention can be achieved through the following technical solutions: The flame-retardant and fire-resistant PVC material used in the preparation of the new national standard electric vehicle saddle is obtained by melt extrusion of a composite polyvinyl chloride material. The composite polyvinyl chloride material comprises the following raw materials in parts by weight: 100 parts composite flame-retardant polyvinyl chloride, 7-12 parts fire-resistant borosilicate aluminum gel, 18-25 parts dioctyl phthalate, 4-7 parts epoxidized soybean oil, 2-3 parts calcium stearate, and 0.3-0.8 parts antioxidant 1010. The composite flame-retardant polyvinyl chloride is a modified polyvinyl chloride flame-retardant body containing a silicon-oxygen structure, a phosphorus-nitrogen flame-retardant structure, and a phosphorus-oxygen-zirconia coordination structure. The refractory borosilicate aluminate gel is a composite heat-resistant gel particle containing a silicon-oxygen network, a boron-oxygen structure, and an aluminum-oxygen inorganic phase.
[0008] Furthermore, the preparation method of the composite flame-retardant polyvinyl chloride is as follows: flexible modified polyvinyl chloride is added to a mixing reactor and heated to plasticize. After uniform plasticization, synergistic flame-retardant silicon zirconium powder is added and stirred and dispersed. Then, dibutyltin dilaurate is added, and the mixing reactor is heated to 150-165℃ and stirred for 2.5-3.5 hours. The composite flame-retardant polyvinyl chloride is obtained after post-treatment.
[0009] Furthermore, the ratio of the flexible modified polyvinyl chloride, the synergistic flame-retardant silicon zirconium powder, and dibutyltin dilaurate is 90-110g:13-18g:0.8-1.2mL. The post-treatment includes: maintaining stirring under vacuum for 15-25min after the reaction is completed, cooling to room temperature, crushing and granulating the material to obtain composite flame-retardant polyvinyl chloride with a particle size of 1-3mm.
[0010] Furthermore, the preparation method of the flexible modified polyvinyl chloride is as follows: polyvinyl chloride resin, cyclohexanone, hydroxyethyl acrylate and maleic anhydride are added to a reaction vessel, stirred under nitrogen protection, and after stirring evenly, dicumyl peroxide is added. The reaction vessel is then heated to 115-125℃ and stirred for 3.5-4.5 hours. The flexible modified polyvinyl chloride is obtained after post-treatment.
[0011] Furthermore, the ratio of polyvinyl chloride resin, cyclohexanone, hydroxyethyl acrylate, maleic anhydride, and dicumyl peroxide is 90-110g:180-220mL:9-12mL:5-6g:0.7-1.0g. The post-treatment includes: cooling the reaction solution to below 40°C after the reaction, precipitating it in methanol, filtering and collecting the precipitate, washing the precipitate three times with methanol, and then drying it in a vacuum drying oven at 70-80°C for 8-10 hours to obtain flexible modified polyvinyl chloride.
[0012] Furthermore, the preparation method of the synergistic flame-retardant silicon zirconium powder is as follows: ammonium polyphosphate, melamine and anhydrous ethanol are added to a reaction vessel and stirred. After stirring evenly, aminopropyl-terminated polydimethylsiloxane is added, followed by the dropwise addition of 10wt% zirconium oxychloride aqueous solution. The dropwise addition time is controlled at 40-60 min. During the dropwise addition, 10wt% ammonia water is used to control the pH of the system at 7.5-8.0. After the dropwise addition is completed, the reaction vessel is heated to 75-85℃ and stirred for 5-7 h. The synergistic flame-retardant silicon zirconium powder is then obtained through post-treatment.
[0013] Furthermore, the ratio of the amount of ammonium polyphosphate, melamine, anhydrous ethanol, aminopropyl-terminated polydimethylsiloxane, and 10wt% zirconium oxychloride aqueous solution is 36-44g:13-17g:135-165mL:27-33mL:135-165mL. The post-treatment includes: after the reaction is completed, filtering and collecting the filter cake, washing the filter cake with deionized water and anhydrous ethanol in sequence, drying the filter cake in a vacuum drying oven at 80℃ for 10-14h, and pulverizing it through a 200-mesh sieve to obtain synergistic flame-retardant silicon zirconium powder.
[0014] Furthermore, the preparation method of the refractory borosilicate alumina gel is as follows: 30wt% sodium silicate aqueous solution and deionized water are added to the reaction vessel and stirred. After stirring evenly, boric acid and alumina nanoparticles are added, and then 10wt% hydrochloric acid aqueous solution is added dropwise to adjust the pH of the system to 8.0-8.8. The reaction vessel is heated to 55-65℃ and stirred for 7-9 hours. The refractory borosilicate alumina gel is obtained after post-treatment.
[0015] Furthermore, the ratio of the 30wt% sodium silicate aqueous solution, deionized water, boric acid, and alumina nanoparticles is 180-220mL:70-90mL:19-22g:19-22g. The post-treatment includes: after the reaction is completed, filtering and collecting the gel solid, washing the gel solid with deionized water until the filtrate is neutral, then drying it in a drying oven at 110-125℃ for 8-12 hours, and grinding it through a 200-mesh sieve to obtain refractory borosilicate alumina gel.
[0016] Furthermore, the melt extrusion includes: adding the composite polyvinyl chloride material to a mixer at a temperature of 80-90℃ and stirring it; after stirring evenly, adding it to a twin-screw extruder for melt extrusion; cooling and granulating after extrusion to obtain flame-retardant and fire-resistant PVC material with a particle size of 2-4mm.
[0017] Furthermore, the temperature of the twin-screw extruder is 145-155℃ in zone one, 160-170℃ in zone two, 170-180℃ in zone three, 175-185℃ in the die head, and the screw speed is 100-140 rpm.
[0018] The present invention has the following beneficial effects: 1. The composite flame-retardant polyvinyl chloride prepared by this invention undergoes pre-modification and composite treatment, which pre-stabilizes the flame-retardant functional structure within the PVC matrix. This avoids the local enrichment caused by the direct addition of flame-retardant components during the final blending process and enables the material to form a more continuous flame-retardant response when heated. After the refractory borosilicate alumina gel is further dispersed in the matrix, its inorganic refractory structure can connect with the barrier structure formed by the composite flame-retardant polyvinyl chloride when heated, thus continuously restricting the heat transfer and the escape of combustible decomposition products in the combustion zone. The combination of the two is not a simple superposition of flame-retardant component content, but rather the formation of a mutually complementary protective structure at different heating stages, making it difficult for the material to maintain continuous combustion and suppressing flame spread. At the same time, the reinforcement of the heated surface structure by the refractory borosilicate alumina gel allows the flame-retardant effect of the composite flame-retardant polyvinyl chloride itself to be more fully maintained.
[0019] 2. The fire-resistant borosilicate aluminum gel prepared by this invention has a composite inorganic structure composed of boron, silicon, and aluminum distributed inside the PVC material. Under continuous high temperature, it can maintain a relatively stable solid phase and provide support for the residual structure of the material after heating. The composite flame-retardant polyvinyl chloride, which has already completed the composite of the flame-retardant functional phase and the modified PVC matrix in the previous processing, can form a relatively uniform carbon-containing residual structure during thermal decomposition, providing a continuous adhesion and support area for the fire-resistant borosilicate aluminum gel. The two thus form a composite structure in which the organic residual phase and the inorganic refractory phase penetrate each other, reducing local shrinkage, cracking and structural loosening under high temperature. This structure retains more high-temperature residues and can also delay the continued thermal decomposition of the internal material, so that the high-temperature stabilizing effect of the fire-resistant borosilicate aluminum gel and the carbonization barrier properties of the composite flame-retardant polyvinyl chloride form a continuous combination.
[0020] 3. During the formation process, the flexible modified PVC matrix and flame-retardant functional phase are pre-composite, so that the rigid functional components no longer directly enter the final system in a simple physical filling state. When the material is subjected to tension, bending and local loads, it can maintain a relatively continuous stress transmission path. After the addition of refractory borosilicate alumina gel, its dispersion in the above-mentioned composite matrix is well supported. In combination with the plasticizing and regulating system composed of dioctyl phthalate and epoxidized soybean oil, it reduces the local rigidification and stress concentration caused by the introduction of inorganic refractory components. This allows the material to maintain flexible deformation and tear resistance suitable for saddle covering. At the same time, the relatively stable matrix-inorganic phase interface reduces the functional phase separation and local defects caused by repeated deformation. This ensures that the protective structure formed by refractory borosilicate alumina gel and composite flame-retardant PVC still has good continuity after the material is deformed. Attached Figure Description
[0021] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0022] Figure 1 This is a SEM image of the synergistic flame-retardant silicon-zirconium powder prepared in Example 3 of the present invention; Figure 2 This is a SEM image of the refractory borosilicate aluminate gel prepared in Example 6 of the present invention; Figure 3 This is a SEM image of the cross-section of the composite flame-retardant polyvinyl chloride material prepared in Example 6 of the present invention.
[0023] like Figure 1 As shown, the obtained synergistic flame-retardant silicon zirconium powder is in the form of irregular particles with a rough surface and fine particles attached, indicating that a composite deposition structure is formed after the reaction. There is some agglomeration between the particles, but no large dense clumps are observed overall. The powder has good dispersibility. Combined with sieving, the sample particle size is in the fine powder range, which is conducive to its uniform dispersion in the PVC matrix and enhances the interfacial bonding. like Figure 2 As shown, the refractory borosilicate alumina gel exhibits irregular block and granular morphology with a rough surface and obvious wrinkles, pores, and fine particle attachment structures. The bonding between different regions is relatively tight, and no obvious large-scale phase separation is observed, indicating that the gel components have good composite uniformity. This multi-scale rough structure can increase the interfacial contact area, which is beneficial to its dispersion in the PVC matrix and provides a structural basis for the formation of a continuous and stable inorganic refractory layer at high temperatures. like Figure 3As shown, the cross-section of the composite flame-retardant and fire-resistant PVC material is relatively dense, with good matrix continuity. No obvious through cracks or large-scale pores were observed. The inorganic gel and flame-retardant components were dispersed relatively evenly in the matrix. Fine particles were embedded in the polymer phase in some areas. The interface bonding was relatively tight, and no obvious debonding phenomenon was observed. The above morphology indicates that the components have good compatibility and dispersion effects, which is conducive to the synergistic effect of the material's flame retardancy, fire resistance and mechanical properties. Detailed Implementation
[0024] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0025] In this application, the polyvinyl chloride resin used is a suspension polyvinyl chloride resin with an average degree of polymerization of 1000-1100, a K value of 65-67, and an apparent density of 0.45-0.55 g / cm³. 3 The volatile matter content is ≤0.30wt%; the ammonium polyphosphate used is type II ammonium polyphosphate with a degree of polymerization ≥1000, phosphorus content of 31.0-32.0wt%, nitrogen content of 14.0-15.0wt%, average particle size D50 of 10-15μm, and moisture content ≤0.30wt%; the aminopropyl-terminated polydimethylsiloxane used is biaminopropyl-terminated polydimethylsiloxane with a dynamic viscosity of 100-300mPa·s at 25℃, a number-average molecular weight of 3000-5000g / mol, and an amino content of 0.6-1.0mmol / g; the alumina nanopowder used is γ-alumina nanopowder with a purity ≥99.5wt%, an average particle size of 20-40nm, and a specific surface area of 100-150m². 2 / g, moisture content ≤0.5wt%.
[0026] Example 1 This embodiment provides a method for preparing composite flame-retardant polyvinyl chloride, including the following steps: Step ①: Preparation of synergistic flame-retardant silicon-zirconium powder Weigh out 36.0 g of ammonium polyphosphate, 13.0 g of melamine, and 135.0 mL of anhydrous ethanol and add them to the reaction vessel. Stir until homogeneous, then add 27.0 mL of aminopropyl-terminated polydimethylsiloxane, followed by 135.0 mL of 10 wt% zirconium oxychloride aqueous solution. The addition time is controlled at 40 min. During the addition, 10 wt% ammonia water is used to control the pH of the system at 7.5. After the addition is complete, heat the reaction vessel to 75 °C and stir for 5 h. After the reaction is complete, filter and collect the filter cake. Wash the filter cake with deionized water and anhydrous ethanol in sequence. Place the filter cake in a vacuum drying oven at 80 °C and dry for 10 h. Crush and pass through a 200-mesh sieve to obtain synergistic flame-retardant zirconium silicon powder.
[0027] The reaction principle for preparing synergistic flame-retardant silicon-zirconium powder is as follows: Ammonium polyphosphate and melamine provide phosphorus- and nitrogen-containing components, which are dispersed in an alcohol-water mixture to form a composite component. Aminopropyl-terminated polydimethylsiloxane introduces amino-containing siloxane segments to participate in the construction of the organosilicon component in the system. Zirconium oxychloride undergoes hydrolysis under aqueous and weakly alkaline conditions to form an inorganic component with a zirconium-oxygen structure, which combines and deposits with the phosphate structure in ammonium polyphosphate. After a heat-preserving reaction, the phosphorus- and nitrogen-containing components, organosilicon components, and zirconium-containing components in the system together form a composite solid. After filtration, washing, drying, and sieving, synergistic flame-retardant silicon-zirconium powder is obtained.
[0028] Step 2: Preparation of flexible modified polyvinyl chloride Weigh out 90.0g of polyvinyl chloride resin, 180.0mL of cyclohexanone, 9.0mL of hydroxyethyl acrylate and 5.0g of maleic anhydride and add them to the reaction vessel. Stir under nitrogen protection. After stirring evenly, add 0.7g of dicumyl peroxide and heat the reaction vessel to 115℃ and stir for 3.5h. After the reaction is completed, cool the reaction solution to below 40℃, pour it into methanol for precipitation, filter and collect the precipitate, wash the precipitate three times with methanol, and then dry it in a vacuum drying oven at 70℃ for 8h to obtain flexible modified polyvinyl chloride.
[0029] The reaction principle for preparing flexible modified polyvinyl chloride is as follows: Polyvinyl chloride (PVC) resin is in a swollen and dispersed state in cyclohexanone. Hydroxyethyl acrylate and maleic anhydride, as unsaturated modified monomers, are distributed in the PVC system. Dicumyl peroxide decomposes upon heating to generate free radicals, which initiate a free radical reaction between hydroxyethyl acrylate and maleic anhydride, introducing segments containing hydroxyl and anhydride structures into the PVC system. After the reaction is complete, the reaction solution is poured into methanol, causing the polymer components to precipitate from the reaction medium. After washing and drying, flexible modified PVC with polar modified structures is obtained.
[0030] Step ③: Preparation of composite flame-retardant polyvinyl chloride Weigh 90.0g of flexible modified polyvinyl chloride and add it to a mixing reactor. Heat and plasticize the mixture. After uniform plasticization, add 13.0g of synergistic flame-retardant silicon zirconium powder and continue stirring to disperse. Then add 0.8mL of dibutyltin dilaurate. Heat the mixing reactor to 150℃ and stir for 2.5h. After the reaction is complete, maintain stirring under vacuum for 15min. Cool to room temperature, crush and granulate the material to obtain composite flame-retardant polyvinyl chloride with a particle size of 1mm.
[0031] The reaction principle for preparing composite flame-retardant polyvinyl chloride is as follows: Under intensive mixing and heating conditions, flexible modified polyvinyl chloride (PVC) undergoes plasticization, increasing the mobility of polymer chain segments. Synergistic flame-retardant silicon zirconium powder disperses into the PVC molten system under shearing action. The polar groups such as hydroxyl and anhydride-derived structures in the flexible modified PVC form an interface bond with the phosphorus-containing, silicon-containing, and zirconium-containing structures on the surface of the synergistic flame-retardant silicon zirconium powder. Dibutyltin dilaurate, as an organotin component, participates in the interface regulation of the polar structure in the system. After intensive mixing, vacuum stirring, cooling, and granulation, a composite flame-retardant PVC composed of PVC phase and synergistic flame-retardant silicon zirconium powder is formed.
[0032] The mechanism of action of composite flame-retardant polyvinyl chloride in composite flame-retardant polyvinyl chloride is as follows: The composite flame-retardant PVC obtained by this process uses flexible modified PVC as the continuous matrix and synergistic flame-retardant silicon zirconium powder as the functional dispersed phase. The interface between the two phases is adjusted by an organotin component. The flexible segments in the flexible modified PVC endow the system with good deformation ability, while its polar groups such as hydroxyl and anhydride-derived structures provide interfacial binding sites for flame-retardant particles, which is beneficial to improving the dispersion stability and stress transfer ability of the functional phase. The phosphorus component in the synergistic flame-retardant silicon zirconium powder promotes charring upon heating, the silicon component improves the dense thermal insulation effect of the residual layer, and the zirconium component enhances the thermal stability and support capacity of the high-temperature residual structure. The organotin component further improves the interfacial compatibility between the particles and the polymer matrix, thereby forming a composite structure in which the continuous organic phase and the stable flame-retardant functional phase work together. While maintaining the material's flexibility, elongation at break, and tear resistance, it can inhibit the migration of heat and combustible decomposition products, improve the limiting oxygen index, high-temperature residual mass rate, and overall flame-retardant and fire-resistant stability.
[0033] Example 2 This embodiment provides a method for preparing composite flame-retardant polyvinyl chloride, including the following steps: Step ①: Preparation of synergistic flame-retardant silicon-zirconium powder Weigh out 44.0 g of ammonium polyphosphate, 17.0 g of melamine, and 165.0 mL of anhydrous ethanol and add them to the reaction vessel. Stir until homogeneous, then add 33.0 mL of aminopropyl-terminated polydimethylsiloxane, followed by dropwise addition of 165.0 mL of 10 wt% zirconium oxychloride aqueous solution over a period of 60 min. During the dropwise addition, use 10 wt% ammonia water to control the pH of the system at 8.0. After the dropwise addition is complete, heat the reaction vessel to 85 °C and stir for 7 h. After the reaction is complete, filter and collect the filter cake. Wash the filter cake with deionized water and anhydrous ethanol in sequence. Place the filter cake in a vacuum drying oven at 80 °C and dry for 14 h. Crush the filter cake and pass it through a 200-mesh sieve to obtain synergistic flame-retardant zirconium silicon powder.
[0034] Step 2: Preparation of flexible modified polyvinyl chloride Weigh out 110.0g of polyvinyl chloride resin, 220.0mL of cyclohexanone, 12.0mL of hydroxyethyl acrylate and 6.0g of maleic anhydride and add them to the reaction vessel. Stir under nitrogen protection. After stirring evenly, add 1.0g of dicumyl peroxide and heat the reaction vessel to 125℃ and stir for 4.5h. After the reaction is completed, cool the reaction solution to below 40℃, pour it into methanol for precipitation, filter and collect the precipitate, wash the precipitate three times with methanol, and then dry it in a vacuum drying oven at 80℃ for 10h to obtain flexible modified polyvinyl chloride.
[0035] Step ③: Preparation of composite flame-retardant polyvinyl chloride Weigh 110.0g of flexible modified polyvinyl chloride and add it to a mixing reactor. Heat and plasticize the mixture. After uniform plasticization, add 18.0g of synergistic flame-retardant silicon zirconium powder and continue stirring to disperse. Then add 1.2mL of dibutyltin dilaurate. Heat the mixing reactor to 165℃ and stir for 3.5h. After the reaction is complete, maintain stirring under vacuum for 25min. Cool to room temperature, crush and granulate the material to obtain composite flame-retardant polyvinyl chloride with a particle size of 3mm.
[0036] Example 3 This embodiment provides a method for preparing composite flame-retardant polyvinyl chloride, including the following steps: Step ①: Preparation of synergistic flame-retardant silicon-zirconium powder Weigh out 40.0g of ammonium polyphosphate, 15.0g of melamine, and 150.0mL of anhydrous ethanol and add them to the reaction vessel. Stir until homogeneous, then add 30.0mL of aminopropyl-terminated polydimethylsiloxane, followed by 150.0mL of 10wt% zirconium oxychloride aqueous solution. The addition time is controlled at 50min. During the addition, 10wt% ammonia water is used to control the pH of the system at 7.8. After the addition is complete, heat the reaction vessel to 80℃ and stir for 6h. After the reaction is complete, filter and collect the filter cake. Wash the filter cake with deionized water and anhydrous ethanol in sequence. Place the filter cake in a vacuum drying oven at 80℃ and dry for 12h. Crush and pass through a 200-mesh sieve to obtain synergistic flame-retardant zirconium silicon powder.
[0037] Step 2: Preparation of flexible modified polyvinyl chloride Weigh out 100.0g of polyvinyl chloride resin, 200.0mL of cyclohexanone, 10.5mL of hydroxyethyl acrylate and 5.5g of maleic anhydride and add them to the reaction vessel. Stir under nitrogen protection. After stirring evenly, add 0.9g of dicumyl peroxide and heat the reaction vessel to 120℃ and stir for 4.0h. After the reaction is completed, cool the reaction solution to below 40℃, pour it into methanol for precipitation, filter and collect the precipitate, wash the precipitate 3 times with methanol, and then dry it in a vacuum drying oven at 75℃ for 9h to obtain flexible modified polyvinyl chloride.
[0038] Step ③: Preparation of composite flame-retardant polyvinyl chloride Weigh 100.0g of flexible modified polyvinyl chloride and add it to a mixing reactor. Heat and plasticize the mixture. After uniform plasticization, add 15.5g of synergistic flame-retardant silicon zirconium powder and continue stirring to disperse. Then add 1.0mL of dibutyltin dilaurate. Heat the mixing reactor to 158℃ and stir for 3.0h. After the reaction is completed, maintain stirring under vacuum for 20min. Cool to room temperature, crush and granulate the material to obtain composite flame-retardant polyvinyl chloride with a particle size of 2mm.
[0039] Example 4 This embodiment provides a method for preparing flame-retardant and fire-resistant PVC material for the fabrication of saddles for electric vehicles meeting new national standards, including the following steps: Step 1: Preparation of Refractory Borosilicate Aluminum Gel Weigh out 180.0 mL of 30 wt% sodium silicate aqueous solution and 70.0 mL of deionized water and add them to the reaction vessel. Stir until homogeneous, then add 19.0 g of boric acid and 19.0 g of alumina nanoparticles. Add 10 wt% hydrochloric acid aqueous solution to adjust the pH of the system to 8.0. Heat the reaction vessel to 55℃ and stir for 7 h. After the reaction is complete, filter and collect the gel solid. Wash the gel solid with deionized water until the filtrate is neutral. Then place it in a drying oven at 110℃ and dry for 8 h. Grind it through a 200-mesh sieve to obtain refractory borosilicate alumina gel.
[0040] The reaction principle for preparing refractory borosilicate alumina gel is as follows: After adjusting the pH of the sodium silicate aqueous solution with hydrochloric acid, the silicate structure undergoes hydrolysis and condensation to generate a gel structure with silicon-oxygen bonds as the main linkage. Boric acid forms a boron-oxygen structure in this aqueous system and together with the silicon-oxygen gel system, it forms a borosilicate composite structure. Alumina nanoparticles are dispersed in the gel system as an aluminum-oxygen inorganic component. The hydroxyl groups on their surface form an interface bond with the silicon-oxygen and boron-oxygen structures. After a heat preservation reaction, the system forms an inorganic gel solid containing silicon, boron, and aluminum components. After washing, drying, grinding, and sieving, refractory borosilicate alumina gel is obtained.
[0041] The mechanism of action of fire-resistant borosilicate alumina gel in composite flame-retardant polyvinyl chloride is as follows: The refractory borosilicate alumina gel obtained by this process has a silicon-oxygen network as its main framework, with boron-oxygen structures interconnected with the silicon-oxygen structure. Nano-alumina provides inorganic reinforcement and high-temperature support. The silicon-oxygen framework has high thermal stability and can form a stable inorganic barrier structure when the material is heated. The boron-oxygen structure helps to improve the densification ability of the borosilicate network, allowing the inorganic phase formed at high temperatures to fill the pores and microcracks in the residual layer, reducing the transfer of heat and decomposition products. The alumina component strengthens the gel framework through interfacial bonding, improving the strength, heat resistance, and shrinkage resistance of the residual structure. When introduced into composite flame-retardant polyvinyl chloride, the borosilicate alumina inorganic phase can form a synergistic barrier with the flame-retardant system, making the heated residual layer more continuous, dense, and stable, reducing cracking and structural collapse under high temperature, thereby reducing the combustion spread rate, improving the high-temperature residual mass rate and refractory stability, and improving the overall structural integrity of the material through fine particle filling and structural support.
[0042] Step 2: Preparation of flame-retardant and fire-resistant PVC material Weigh out the following by weight: 100 parts of the composite flame-retardant polyvinyl chloride prepared in Example 1, 7.0 parts of fire-resistant borosilicate alumina gel, 18.0 parts of dioctyl phthalate, 4.0 parts of epoxidized soybean oil, 2.0 parts of calcium stearate and 0.3 parts of antioxidant 1010, and mix them to obtain the composite polyvinyl chloride material. The composite polyvinyl chloride material was added to a mixer at 80°C and stirred until uniform. Then, it was added to a twin-screw extruder for melt extrusion. The temperature of the twin-screw extruder was 145°C in zone one, 160°C in zone two, 170°C in zone three, and 175°C in the die head. The screw speed was 100 rpm. After extrusion, the material was cooled and granulated to obtain flame-retardant and fire-resistant PVC material with a particle size of 2 mm.
[0043] The reaction principle for preparing flame-retardant and fire-resistant PVC materials is as follows: Composite flame-retardant polyvinyl chloride (PVC), fire-resistant borosilicate alumina gel, dioctyl phthalate, epoxidized soybean oil, calcium stearate, and antioxidant 1010 are mixed according to a set weight ratio to form a PVC composite formulation system. During the heating and mixing process, dioctyl phthalate and epoxidized soybean oil are dispersed between the PVC molecular chains, while calcium stearate and antioxidant 1010 are distributed in the polymer system. Fire-resistant borosilicate alumina gel, as an inorganic gel component, is mixed together with the composite flame-retardant PVC. During the twin-screw extrusion process, the material is further plasticized, dispersed, and shaped under the action of heat and shear. After cooling and granulation, flame-retardant and fire-resistant PVC material is obtained.
[0044] Example 5 This embodiment provides a method for preparing flame-retardant and fire-resistant PVC material for the fabrication of saddles for electric vehicles meeting new national standards, including the following steps: Step 1: Preparation of Refractory Borosilicate Aluminum Gel Weigh 220.0 mL of 30 wt% sodium silicate aqueous solution and 90.0 mL of deionized water and add them to the reaction vessel. Stir until homogeneous, then add 22.0 g of boric acid and 22.0 g of alumina nanoparticles. Add 10 wt% hydrochloric acid aqueous solution to adjust the pH of the system to 8.8. Heat the reaction vessel to 65 ℃ and stir for 9 h. After the reaction is complete, filter and collect the gel solid. Wash the gel solid with deionized water until the filtrate is neutral. Then dry it in a drying oven at 125 ℃ for 12 h. Grind it through a 200 mesh sieve to obtain refractory borosilicate alumina gel.
[0045] Step 2: Preparation of flame-retardant and fire-resistant PVC material Weigh out the following by weight: 100 parts of the composite flame-retardant polyvinyl chloride prepared in Example 2, 12.0 parts of fire-resistant borosilicate alumina gel, 25.0 parts of dioctyl phthalate, 7.0 parts of epoxidized soybean oil, 3.0 parts of calcium stearate and 0.8 parts of antioxidant 1010, and mix them to obtain the composite polyvinyl chloride material. The composite polyvinyl chloride material was added to a mixer at a temperature of 90℃ and stirred until uniform. Then, it was added to a twin-screw extruder for melt extrusion. The temperature of the twin-screw extruder was 155℃ in zone one, 170℃ in zone two, 180℃ in zone three, 185℃ in the die head, and the screw speed was 140 rpm. After extrusion, the material was cooled and granulated to obtain flame-retardant and fire-resistant PVC material with a particle size of 4 mm.
[0046] Example 6 This embodiment provides a method for preparing flame-retardant and fire-resistant PVC material for the fabrication of saddles for electric vehicles meeting new national standards, including the following steps: Step 1: Preparation of Refractory Borosilicate Aluminum Gel Weigh 200.0 mL of 30 wt% sodium silicate aqueous solution and 80.0 mL of deionized water and add them to the reaction vessel. Stir until homogeneous, then add 20.5 g of boric acid and 20.5 g of alumina nanoparticles. Add 10 wt% hydrochloric acid aqueous solution to adjust the pH of the system to 8.4. Heat the reaction vessel to 60 ℃ and stir for 8 h. After the reaction is complete, filter and collect the gel solid. Wash the gel solid with deionized water until the filtrate is neutral. Then dry it in a drying oven at 118 ℃ for 10 h. Grind it through a 200 mesh sieve to obtain refractory borosilicate alumina gel.
[0047] Step 2: Preparation of flame-retardant and fire-resistant PVC material Weigh out the following by weight: 100 parts of the composite flame-retardant polyvinyl chloride prepared in Example 3, 9.5 parts of fire-resistant borosilicate alumina gel, 21.5 parts of dioctyl phthalate, 5.5 parts of epoxidized soybean oil, 2.5 parts of calcium stearate and 0.6 parts of antioxidant 1010, and mix them to obtain the composite polyvinyl chloride material. The composite polyvinyl chloride material was added to a mixer at 85°C and stirred until uniform. Then, it was added to a twin-screw extruder for melt extrusion. The temperature of the twin-screw extruder was 150°C in zone one, 165°C in zone two, 175°C in zone three, 180°C in the die head, and the screw speed was 120 rpm. After extrusion, the material was cooled and granulated to obtain flame-retardant and fire-resistant PVC material with a particle size of 3 mm.
[0048] Comparative Example 1 The difference between this comparative example and Example 6 is that, in step 2, the composite flame-retardant polyvinyl chloride used in step 1 of the preparation process is modified by omitting the addition of aminopropyl-terminated polydimethylsiloxane and 10wt% zirconium oxychloride aqueous solution.
[0049] Comparative Example 2 The difference between this comparative example and Example 6 is that, in the preparation process of the composite flame-retardant polyvinyl chloride used in step 2, step ② is omitted, and in step ③, polyvinyl chloride resin is used to replace the flexible modified polyvinyl chloride in an equal amount.
[0050] Comparative Example 2 The difference between this comparative example and Example 6 is that the addition of refractory borosilicate aluminate gel is omitted in step two.
[0051] Performance testing: All test samples were prepared using the flame-retardant and fire-resistant PVC materials obtained in the various examples and comparative examples. Each group of PVC materials was placed in a flatbed hot press and pressed into test sheets. The hot pressing temperature was 175±2℃. After preheating for 3 minutes, the sheets were hot-pressed at 8MPa for 5 minutes. Then, the sheets were cooled to below 40℃ while maintaining the pressure at 8MPa before demolding. The limiting oxygen index test used a sheet with a thickness of 4.0±0.25mm, while the vertical burning, trouser tear, and elongation at break tests used a sheet with a thickness of 0.80±0.05mm. The same hot pressing conditions were used for all examples and comparative examples. Except for thermogravimetric analysis, all samples were conditioned in accordance with GB / T 2918-2018 "Standard Environment for Conditioning and Testing of Plastic Samples", and placed in an environment of 23±2℃ and 50±5% relative humidity for 88 hours. The tests were conducted under the same temperature and humidity conditions. Unless otherwise specified, no less than 5 valid samples were used for each mechanical property test, and 3 parallel samples were used for the vertical burning test. The results were taken as the arithmetic mean.
[0052] The limiting oxygen index (LOI) was determined according to GB / T 2406.2-2009 "Determination of flammability by oxygen index method for plastics - Part 2: Room temperature test". The test result is expressed as the limiting oxygen index (LOI) in percentage terms. The specific test parameters are as follows: A strip sample with a length of 100 mm and a width of 10.0 ± 0.5 mm was cut from a hot-pressed sheet with a thickness of 4.0 ± 0.25 mm. The sample was vertically installed in the combustion chamber of the oxygen indexer. Oxygen and nitrogen were used as a mixed gas, and the test was conducted using a top-side ignition method. The flow rate of the mixed gas in the combustion chamber was controlled at 40 ± 10 mm / s. A new sample was replaced each time the oxygen volume fraction was changed. A complete test sequence was completed according to the oxygen concentration adjustment procedure and combustion criteria specified in GB / T 2406.2-2009. The minimum oxygen volume fraction that could maintain the specified combustion behavior of the sample was determined according to the specified method and was used as the limiting oxygen index of the material group. The test results were accurate to 0.1%.
[0053] The vertical burning rate was determined in accordance with GB / T 32086-2015 "Technical Requirements and Test Methods for Vertical Burning Characteristics of Specific Types of Automotive Interior Materials". The test results are expressed as vertical burning rate, with the unit being mm / min. The specific test parameters are as follows: For comparative evaluation among the materials, hot-pressed sheets with a thickness of 0.80±0.05mm were cut into specimens with a length of 560±2mm and a width of 170±2mm, with 3 specimens tested in each group; the specimens were vertically fixed in the combustion test device using the standard-specified specimen frame, the air velocity in the test area was controlled at 0.10-0.30m / s, the test flame height was 40±2mm, and the burner position and mark position were set according to GB / T 32086-2015. The flame was applied to the specimen for 15s and then removed; the propagation distance and propagation time of the flame within the specified measurement range were recorded, and the vertical combustion rate was calculated according to the standard. If the specimen extinguished itself before reaching the first mark, the corresponding combustion result was recorded according to the standard; the arithmetic mean of the test results of the 3 specimens was taken as the vertical combustion rate of the material group.
[0054] The residual mass percentage at 700℃ was determined according to GB / T 33047.1-2025 "Plastic Polymers - Thermogravimetric Analysis (TG) - Part 1: General Rules". The test result is expressed as the residual mass percentage at 700℃, in % (%). The specific test parameters are as follows: Representative samples were randomly cut from each group of hot-pressed sheets. Each time, 10.0±0.5mg was weighed and placed in a clean, open alumina crucible. Thermogravimetric analysis was used for testing. The test atmosphere was nitrogen with a purity of not less than 99.999%. Before the test, the sample was purged with nitrogen for 20 minutes. During the test, the nitrogen flow rate was maintained at 50mL / min. The initial temperature was 30℃, and the temperature was increased to 800℃ at a constant heating rate of 10℃ / min. The mass of the sample at the beginning of the test was recorded as m0, and the remaining mass at 700℃ was recorded as m700. The residual mass rate at 700℃ was calculated according to m700 / m0×100%. Three parallel tests were performed for each group, and the arithmetic mean was taken as the final result.
[0055] The trouser tear strength was determined in accordance with GB / T 16578.1-2008 "Determination of tear resistance of plastic films and sheets - Part 1: Trouser tear method". The test results are expressed as trouser tear strength, and the unit is kN / m. The specific test parameters are as follows: A rectangular specimen with a length of 150 mm and a width of 50 mm was cut from a hot-pressed sheet with a thickness of 0.80±0.05 mm. A straight cut with a length of 75±1 mm was made along the center line of the length direction from one end of the specimen to form two pant legs. The edges of the specimen and the cut ends were kept flat and without obvious gaps. The thickness was measured at three equidistant locations between the top of the cut and the other end of the specimen, and the average value was taken as the thickness of the specimen. The test was performed using an electronic universal testing machine with an initial clamping distance of 75 mm. The two pant legs were clamped separately. In the upper and lower clamps, the line connecting the main axis of the specimen and the center of the clamp is aligned. The clamp separation speed is set to 200±20 mm / min, and the force value during the tear propagation process is continuously recorded. The average tear force is calculated according to the stable tear stage specified in GB / T16578.1-2008, and the trouser tear strength is calculated by the ratio of the average tear force to the average thickness of the specimen. Five valid specimens are tested in each group. Specimens whose tear paths deviate significantly from the specified tear area and extend to the side of the specimen are discarded and retested. The arithmetic mean of the five valid test results is taken as the final result.
[0056] The elongation at break was determined in accordance with GB / T 1040.1-2025 "Determination of tensile properties of plastics - Part 1: General" and GB / T 1040.3-2006 "Determination of tensile properties of plastics - Part 3: Test conditions for films and sheets". The test results are expressed as elongation at break, in percentage (%). The specific test parameters are as follows: Type 2 strip specimens are cut from hot-pressed sheets with a thickness of 0.80±0.05mm. The total length of the specimen is not less than 150mm and the width is 15.0±0.2mm. An initial gauge length L0 of 50±0.5mm is set in the effective test area of the specimen. The test is conducted using an electronic universal testing machine with an initial clamping distance of 100±5mm and a tensile speed of 200±20mm / min. The specimen is continuously stretched until it breaks after the longitudinal axis of the specimen coincides with the line connecting the centers of the upper and lower clamps. The elongation at break is calculated as the percentage of the difference between the gauge length Lb at the time of specimen breakage and the initial gauge length L0 to the initial gauge length L0, i.e., elongation at break = (Lb-L0) / L0×100%. Five valid specimens are tested in each group. Specimens that break at the clamp, slip significantly, or undergo other abnormal fractures are discarded and retested. The arithmetic mean of the five valid test results is taken as the final result.
[0057] See Table 1 for specific data; Table 1 - Performance Test Data for Each Sample
[0058] Data Analysis: A comparative analysis of the data in Table 1 reveals the following: The flame-retardant PVC material prepared by this invention exhibits excellent flame retardancy, fire resistance stability, and mechanical retention properties. Limiting oxygen index (LOI) tests showed that the LIO of the materials obtained in the examples was 34.7-35.0%, significantly higher than the 30.8-32.6% of the comparative examples, indicating that the composite flame-retardant system constructed in this invention can effectively improve the flame retardancy of the material in an oxygen-rich environment. Vertical burning tests showed that the vertical burning rate of the examples was 41.8-42.6 mm·min. -1 This is significantly lower than the comparative example's 48.7-56.9 mm·min. -1 This indicates that the spread of combustion in the material is effectively suppressed, and the barrier protection effect during the combustion process is more stable. After a high-temperature residual mass rate test at 700℃, the residual mass rate of the material obtained in the example reached 36.8-37.3%, which is higher than the 27.6-33.4% of the comparative example. This indicates that the synergistic flame-retardant silicon-zirconium powder and refractory borosilicate-aluminum gel can promote the formation of a stable residual structure under high-temperature conditions, improving the integrity and heat resistance of the char layer or inorganic residual layer. After a trouser tear strength test, the trouser tear strength of the example was 47.6-48.2 kN·m. -1 This is higher than the 37.9-44.5 kN·m of the comparative example. -1 This indicates that the flexible modified polyvinyl chloride has a good load-bearing and interfacial bonding effect on the functional filler, enabling the material to maintain good tear resistance even after the addition of flame-retardant filler. According to the elongation at break test, the elongation at break of the material obtained in the example was 238-244%, which was higher than that of the comparative example (183-224%). This indicates that while achieving flame retardancy and fire resistance enhancement, the material of the present invention did not significantly sacrifice flexibility due to the introduction of inorganic functional phases. Based on the above test results, it can be seen that the present invention, through the synergistic effect between flexible modified polyvinyl chloride, synergistic flame retardant silicon zirconium powder, and fire-resistant borosilicate aluminum gel, enables the material to simultaneously possess a high limiting oxygen index, a low burning rate, high high-temperature residual stability, and good mechanical properties, demonstrating excellent comprehensive flame retardant and fire-resistant effects.
[0059] After comparing and analyzing the comparative data, we can find that: In Comparative Example 1, after the removal of siloxane regulation and the introduction of zirconium components, the phosphorus and nitrogen components are unable to form a composite structure that combines the adaptability of the organic phase and the stability of the inorganic phase. This affects the dispersion and solid-phase construction ability of the internal functional phase of the composite flame-retardant polyvinyl chloride obtained in step ③. When heated, the barrier residue formed lacks sufficient structural connection with the fire-resistant borosilicate alumina gel, reducing the continuity and density of the composite barrier. Consequently, the flame-retardant stability and fire resistance retention of the material under continuous heat are reduced. In Comparative Example 2, after step ② was cancelled, the PVC matrix used in step ③ lacked the corresponding interface control structure, making it difficult for the synergistic flame-retardant silicon zirconium powder to obtain stable interface bonding and uniform load-bearing during the mixing process. The resulting composite flame-retardant polyvinyl chloride was more prone to forming local interface defects. After further compounding with fire-resistant borosilicate aluminum gel, the synergistic distribution between the functional phases was restricted, and the continuity of stress transmission and heat protection structure was weakened, resulting in a decrease in the material's flexible deformation ability, tear resistance and flame-retardant fire resistance stability. In Comparative Example 3, after the introduction of refractory borosilicate alumina gel in step two was cancelled, the residual structure formed by the composite flame-retardant polyvinyl chloride under heat lost the filling, support and stabilizing effect of the inorganic gel phase, making it difficult to further form a composite barrier in which the organic residual phase and the inorganic refractory phase interpenetrate. Under continuous high temperature, the residual layer is more prone to shrinkage, loosening and local cracking, which weakens its ability to restrict heat transfer and the migration of decomposition products, thus leading to a decrease in the high-temperature structural stability and flame-retardant and fire-resistant continuity of the material.
[0060] Ultimately, this study demonstrates that the performance improvement of this solution does not stem from the simple superposition of single flame-retardant or refractory components. Rather, it is based on the internal structure construction of the composite flame-retardant PVC, the control of the matrix interface, and its synergistic compounding with the refractory borosilicate alumina gel. Damage to any key link will weaken the uniform dispersion of the functional phase, the interfacial bonding, or the solid-phase connection after heating, making it difficult for the final system to form a composite protective structure that combines continuity, density, and stability. This further affects the stress transmission under stress. Therefore, each comparative example showed varying degrees of overall performance decline, which indirectly indicates a clear structural transfer relationship between the preparation steps and a mutually promoting synergistic effect between the composite flame-retardant PVC and the refractory borosilicate alumina gel.
[0061] The above description is merely an example and illustration of the structure of the present invention. Those skilled in the art can make various modifications or additions to the specific embodiments described, or use similar methods to replace them, as long as they do not deviate from the structure of the invention or exceed the scope defined in the claims, all of which should fall within the protection scope of the present invention.
[0062] In the description of this specification, references to terms such as "an embodiment," "example," "specific example," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the invention. In this specification, illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.
[0063] The preferred embodiments of the present invention disclosed above are merely illustrative of the invention. These preferred embodiments do not exhaustively describe all details, nor do they limit the invention to specific implementations. Clearly, many modifications and variations can be made based on the content of this specification. This specification selects and specifically describes these embodiments to better explain the principles and practical applications of the invention, thereby enabling those skilled in the art to better understand and utilize the invention. The invention is limited only by the claims and their full scope and equivalents.
Claims
1. A flame-retardant and fire-resistant PVC material used in the preparation of saddles for electric vehicles meeting the new national standard, characterized in that, The flame-retardant and fire-resistant PVC material is obtained by melt extrusion of composite polyvinyl chloride material, wherein the composite polyvinyl chloride material comprises the following raw materials in parts by weight: 100 parts composite flame-retardant polyvinyl chloride, 7-12 parts fire-resistant borosilicate aluminum gel, 18-25 parts dioctyl phthalate, 4-7 parts epoxidized soybean oil, 2-3 parts calcium stearate and 0.3-0.8 parts antioxidant 1010; The composite flame-retardant polyvinyl chloride is a modified polyvinyl chloride flame-retardant body containing a silicon-oxygen structure, a phosphorus-nitrogen flame-retardant structure, and a phosphorus-oxygen-zirconia coordination structure. The refractory borosilicate aluminate gel is a composite heat-resistant gel particle containing a silicon-oxygen network, a boron-oxygen structure, and an aluminum-oxygen inorganic phase.
2. The flame-retardant and fire-resistant PVC material for the preparation of new national standard electric vehicle saddles according to claim 1, characterized in that, The preparation method of the composite flame-retardant polyvinyl chloride is as follows: flexible modified polyvinyl chloride is added to a mixing reactor and heated to plasticize. After uniform plasticization, synergistic flame-retardant silicon zirconium powder is added and stirred and dispersed. Then, dibutyltin dilaurate is added, and the mixing reactor is heated to 150-165℃ and stirred for 2.5-3.5 hours. The composite flame-retardant polyvinyl chloride is obtained after post-treatment.
3. The flame-retardant and fire-resistant PVC material for the preparation of new national standard electric vehicle saddles according to claim 2, characterized in that, The ratio of the flexible modified polyvinyl chloride, the synergistic flame-retardant silicon zirconium powder, and the dibutyltin dilaurate is 90-110g:13-18g:0.8-1.2mL.
4. The flame-retardant and fire-resistant PVC material for the preparation of new national standard electric vehicle saddles according to claim 2, characterized in that, The preparation method of the flexible modified polyvinyl chloride is as follows: polyvinyl chloride resin, cyclohexanone, hydroxyethyl acrylate and maleic anhydride are added to a reaction vessel and stirred under nitrogen protection. After stirring evenly, dicumyl peroxide is added, and the reaction vessel is heated to 115-125℃ and stirred for 3.5-4.5 hours. The flexible modified polyvinyl chloride is then obtained after post-treatment.
5. The flame-retardant and fire-resistant PVC material for the preparation of new national standard electric vehicle saddles according to claim 4, characterized in that, The ratio of polyvinyl chloride resin, cyclohexanone, hydroxyethyl acrylate, maleic anhydride and dicumyl peroxide is 90-110g:180-220mL:9-12mL:5-6g:0.7-1.0g.
6. The flame-retardant and fire-resistant PVC material for the preparation of new national standard electric vehicle saddles according to claim 2, characterized in that, The preparation method of the synergistic flame-retardant silicon-zirconium powder is as follows: ammonium polyphosphate, melamine and anhydrous ethanol are added to a reaction vessel and stirred. After stirring evenly, aminopropyl-terminated polydimethylsiloxane is added, followed by dropwise addition of 10wt% zirconium oxychloride aqueous solution. The dropwise addition time is controlled at 40-60 min. During the dropwise addition, 10wt% ammonia water is used to control the pH of the system at 7.5-8.
0. After the dropwise addition is completed, the reaction vessel is heated to 75-85℃ and stirred for 5-7 h. The synergistic flame-retardant silicon-zirconium powder is obtained after post-treatment.
7. The flame-retardant and fire-resistant PVC material for the preparation of new national standard electric vehicle saddles according to claim 6, characterized in that, The ratio of the amounts of ammonium polyphosphate, melamine, anhydrous ethanol, aminopropyl-terminated polydimethylsiloxane, and 10wt% zirconium oxychloride aqueous solution is 36-44g:13-17g:135-165mL:27-33mL:135-165mL.
8. The flame-retardant and fire-resistant PVC material for the preparation of new national standard electric vehicle saddles according to claim 1, characterized in that, The preparation method of the refractory borosilicate alumina gel is as follows: 30wt% sodium silicate aqueous solution and deionized water are added to the reaction vessel and stirred. After stirring evenly, boric acid and alumina nanoparticles are added, and then 10wt% hydrochloric acid aqueous solution is added dropwise to adjust the pH of the system to 8.0-8.
8. The reaction vessel is heated to 55-65℃ and stirred for 7-9 hours. The refractory borosilicate alumina gel is obtained after post-treatment.
9. The flame-retardant and fire-resistant PVC material for the preparation of new national standard electric vehicle saddles according to claim 8, characterized in that, The ratio of the 30wt% sodium silicate aqueous solution, deionized water, boric acid, and alumina nanopowder is 180-220mL:70-90mL:19-22g:19-22g.
10. The flame-retardant and fire-resistant PVC material for the preparation of new national standard electric vehicle saddles according to claim 1, characterized in that, The melt extrusion process includes: adding the composite polyvinyl chloride material to a mixer at a temperature of 80-90℃ and stirring it. After stirring evenly, the mixture is added to a twin-screw extruder for melt extrusion. After extrusion, the mixture is cooled and granulated to obtain flame-retardant and fire-resistant PVC material with a particle size of 2-4mm.